Method for producing spherical silica particles

By using alkaline aqueous silica solution and alkaline substances to prepare spherical silica particles in a mixed solvent, the problems of high cost, uneven particle size and low resin filling in the prior art are solved, and the production of spherical silica particles with low cost, high purity and excellent filling are achieved.

CN119768368AActive Publication Date: 2025-04-04ADMATECHS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202280099553.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-08-30
Publication Date
2025-04-04
Estimated Expiration
2042-08-30

AI Technical Summary

Technical Problem

The prior art is expensive when manufacturing spherical silica particles, the cost is high, the particle size is uneven, and the resin fillability is low. Especially when using TEOS as a raw material, it is expensive and requires high purity TEOS.

Method used

A basic aqueous silica solution is used as a raw material, and spherical silica particles are prepared by using quaternary ammonium and alkali having a cyclic amidine structure as an alkaline substance in a mixed solvent of water and organic solvent, and the preparation and heating process of raw material silica particles is carried out.

Benefits of technology

Low-cost and high-purity spherical silica particles are manufactured, with uniform particle size distribution, excellent fillability, and can adjust the particle size distribution by controlling reaction conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768368A_ABST
    Figure CN119768368A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing a novel method for producing spherical silica particles. Spherical silica particles can be produced using an appropriate mixed solvent using an aqueous alkaline silicic acid solution as a starting material. A method for producing spherical silica particles according to the present invention comprises: a step for preparing starting material silica particles in a mixed solvent of water and an organic solvent, in the presence of an alkaline substance comprising at least one of a quaternary ammonium and a base having a cyclic amidine structure; preparing a dispersion of raw material silica particles from a raw material solution in which silicic acid is dissolved; and a heating step for preparing spherical silica particles by heating the dispersion liquid or the starting material silica particles obtained by solid-liquid separation from the dispersion liquid to remove organic substances contained in the dispersion liquid. The mixed solvent has a relative dielectric constant of 21-40, and a quaternary ammonium derived from the alkaline substance is blended at a blending ratio of 0.3-0.8 in terms of molar ratio with respect to the silicon element derived from the silicic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing spherical silica particles, and more specifically, to a method for producing spherical silica particles by a so-called wet synthesis method. Background Art

[0002] As methods for producing silica particles with high sphericity, there are melting methods, gas phase synthesis methods, and wet synthesis methods. Among them, wet synthesis methods represented by the Stober method have the characteristic of generating less coarse particles, but have high uniformity of particle size and low resin filling properties.

[0003] Furthermore, among the raw materials used in the Stober method, tetraethoxysilane (TEOS) itself is expensive, and in order to obtain high-purity spherical silica particles, high-purity TEOS at a higher cost is required.

[0004] As a method for obtaining spherical porous silica, an emulsion synthesis method using sodium silicate as a raw material has been implemented. However, the raw material contains a lot of sodium, and if washing is performed to reduce the sodium content, there is also a problem of increased cost.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2021-195275 Summary of the invention

[0008] The present invention has been made in view of the above-mentioned actual situation, and a problem to be solved by the present invention is to provide a new method for producing spherical silica particles.

[0009] The present inventors have conducted intensive studies to solve the above problems and have found that spherical silica particles can be produced using an alkaline silicic acid aqueous solution (hereinafter referred to as "alkaline silicic acid aqueous solution") as a raw material. Based on this finding, the present inventors have completed the following invention.

[0010] That is, the method for producing spherical silica particles of the present invention comprises the following steps:

[0011] a raw silica particle preparation step of preparing a dispersion of raw silica particles from a raw material solution in which silicic acid is dissolved in a mixed solvent of water and an organic solvent in the presence of an alkaline substance consisting of at least one of a quaternary ammonium and a base having a cyclic amidine structure; and

[0012] The heating step is to heat the dispersion or the raw silica particles obtained by solid-liquid separation from the dispersion to remove organic matter contained in the dispersion to prepare spherical silica particles. The relative dielectric constant of the mixed solvent is 21 to 40, and the quaternary ammonium from the alkaline substance is mixed at a mixing ratio of 0.3 to 0.8 with respect to the silicon element from the silicic acid in terms of molar ratio.

[0013] Alkaline silicic acid aqueous solution can be prepared by materials such as metallic silicon, silicon dioxide, TEOS, and particularly can be made spherical silicon dioxide particles by materials such as metallic silicon, silicon dioxide, etc. which are often cheaper than TEOS. In addition, these materials easily obtain high purity, and also easily improve the purity of the spherical silicon dioxide particles made. And, the particle size distribution of the obtained spherical silicon dioxide particles can be controlled by reaction conditions, and the spherical silicon dioxide particles with excellent filling property can be made. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a histogram showing the particle size distribution of the test samples of Test Examples 3, 5, 11 and 12 in the Examples.

[0015] Figure 2 This is a SEM photograph of the test sample of Test Example 3 in the examples.

[0016] Figure 3 This is a SEM photograph of the test sample of Test Example 6 in the examples.

[0017] Figure 4 This is a SEM photograph of the test sample of Test Example 8 in the examples.

[0018] Figure 5 This is a SEM photograph of the test sample of Test Example 10 in the Examples.

[0019] Figure 6 This is a cross-sectional SEM photograph of the test sample of Test Example 11 in the Examples.

[0020] Figure 7 This is a SEM photograph of the test sample of Test Example 12 in the Examples.

[0021] Figure 8 This is a SEM photograph of the test sample of Test Example 14 in the Examples.

[0022] Fig. 9 This is a SEM photograph of the test sample of Test Example 17 in the Examples.

[0023] Fig.10 This is a SEM photograph of the test sample of Test Example 18 in the examples.

[0024] Fig.11 This is a cross-sectional SEM photograph of the test sample of Test Example 19 in the Examples.

[0025] Fig.12 This is a SEM photograph of the test sample of Test Example 20 in the Examples. DETAILED DESCRIPTION

[0026] The manufacture method of the spherical silica particles of the present invention is described in detail based on the following embodiments. The spherical silica particles manufactured by the manufacture method of the spherical silica particles of the present embodiment are particles with high sphericity and composed of silica. The spherical silica particles of the present embodiment can be dispersed in a dispersion medium to make a slurry composition, or dispersed in a resin material to make a resin composition. These slurry compositions, resin compositions are preferably used for materials for electronic devices such as substrate materials, sealing materials, bottom filling materials.

[0027] The particle size of the spherical silica particles of this embodiment can be preferably about 100 nm to 10 μm. The sphericity of the spherical silica particles is not particularly limited, but is preferably 0.9 or more, and more preferably 0.95 or more.

[0028] The spherical silica particles may be solid or hollow. Here, the spherical silica particles being solid means that the density of the particles is 2.3 g / cm 3 Above, hollow means that the density of the particles is less than 2.3g / cm 3 In the determination of particle density, the volume of the particle is measured by the constant volume expansion method using nitrogen. The volume of the voids that cannot be penetrated by nitrogen can be measured. The density of the particle including such voids is less than 2.3 g / cm 3 The spherical silica particles are hollow particles. The voids present in the particles may be one or more. In addition, when the particles are so-called porous particles having a plurality of extremely fine voids and the voids cannot be observed even with an electron microscope, the particles are still considered hollow particles.

[0029] The method for producing spherical silica particles according to the present embodiment includes a raw material silica particle preparation step, a heating step, and other steps adopted as necessary.

[0030] (Raw material silicon dioxide particle preparation process)

[0031] The raw silica particle preparation step is a step of precipitating raw silica particles, which are the basis of spherical silica particles, from silicic acid contained in a raw material solution in the presence of an alkaline substance in a mixed solvent of water and an organic solvent to prepare a dispersion. The precipitated raw silica particles are substantially the same as the manufactured spherical silica particles, but contain more water, organic matter, etc.

[0032] The precipitation of the raw silica particles is preferably performed while stirring. The temperature during the precipitation is not particularly limited, but the lower limit thereof may be 0°C, and the upper limit thereof may be 40°C, 50°C, or 60°C.

[0033] The concentration of silicic acid in the raw material solution is not particularly limited. Based on the overall mass and in terms of oxide (SiO2: silicon dioxide) conversion, the lower limit may be 1%, 2%, 3%, 5%, and the upper limit may be 8%, 10%, 15%, and 17%. In order to obtain the necessary concentration, dilution may be performed with water, an organic solvent, or a mixed solvent of water and an organic solvent. Here, oxide conversion refers to a value calculated assuming that all silicon elements contained are in the form of oxides. The raw material solution may contain other metal compounds besides silicic acid. As other metal compounds that may be contained, water-soluble compounds, metal oxides with a particle size of less than 100 nm (particularly metal oxides with a particle size of less than 50 nm, less than 30 nm, or less than 10 nm) may be contained. Other metal oxides can be mixed in when silicic acid is precipitated and particleized to form composite oxides, etc.

[0034] In addition, the precipitation of the raw silica particles is preferably carried out under a state adjusted to a prescribed pH. It is preferably adjusted to a prescribed pH by adding an alkaline substance or an organic acid such as acetic acid. As the prescribed pH, 7.0, 7.5, and 7.8 can be exemplified as lower limits, and 10.0, 9.5, 9.0, 8.5, and 8.2 can be exemplified as upper limits.

[0035] Here, the relative dielectric constant of the mixed solvent is 21 to 40. As the relative dielectric constant, 38, 35, and 33 can be used as the upper limit, and 21.5, 23, and 25 can be used as the lower limit. These upper and lower limits can be combined arbitrarily. Here, the relative dielectric constant of the mixed solvent refers to the relative dielectric constant calculated in the form of a mixed solvent consisting only of the contained water and organic solvent. Specifically, it is obtained by the weighted average of the relative dielectric constant of water and the relative dielectric constant of the mixed organic solvent in the volume ratio.

[0036] The organic solvent may be mixed with water, and the relative dielectric constant after mixing is within the above range. Preferred organic solvents include ketones, esters, and alcohols, and in particular, acetone, methyl ethyl ketone, ethyl acetate, etc. may be used alone or as a mixture, and acetone is more preferably used. The mixing ratio of the organic solvent to water is set so that the relative dielectric constant is within the above range when the mixed solvent is prepared.

[0037] The alkaline substance is composed of at least one of a quaternary ammonium and a base having a cyclic amidine structure. They are not particularly limited, and the quaternary ammonium is preferably selected from quaternary ammoniums having 4 to 16 carbon atoms, and in particular, tetramethylammonium having 4 carbon atoms, tetraethylammonium having 8 carbon atoms, and tetrabutylammonium having 16 carbon atoms can be exemplified. Quaternary ammonium usually has a certain anion as a counterion. For example, tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), and tetrabutylammonium hydroxide (TBAOH) having hydroxide ions, and tetramethylammonium chloride, tetraethylammonium chloride, and tetrabutylammonium chloride having chloride ions can be cited. Examples of the base having a cyclic amidine structure include diazabicycloundecene (DBU) and diazabicyclononene (DBN).

[0038] The alkaline substance is contained in a ratio of 0.3 to 0.8 based on the molar number of silicon element from silicic acid, and its lower limit can be 0.35, 0.4, and the upper limit can be 0.75, 0.7, 0.6. These upper and lower limits can be combined arbitrarily. By making the addition amount of the alkaline substance above the lower limit, the particle size of the raw silica particles manufactured becomes larger and does not form agglomerates, or the density of silica in the raw silica particles manufactured becomes higher. By making the addition amount below the upper limit, oligomerization can be prevented and particleization can be effectively performed. If the density of silica becomes low, there is a tendency that it shrinks due to heating in the heating step described later, or when the spherical silica particles obtained are made into porous particles or hollow particles, the porosity becomes larger.

[0039] The alkaline substance may be added to the mixed solvent before or after the silicic acid. Furthermore, the alkaline substance may be added in divided portions rather than in a single addition.

[0040] The concentration of silicic acid in the raw material solution is not particularly limited, but the upper limit is preferably 0.1%, 0.2%, 0.3%, 0.4%, and the lower limit is preferably 1.0%, 1.5%, 2.0%, 3.0% in terms of oxide conversion based on the mass of the raw material solution. Silicic acid is preferably supplied in the form of an alkaline silicic acid aqueous solution obtained by any of the following methods a) to c). These steps a) to c) are preferably carried out while stirring. An appropriate amount of an organic solvent and an alkaline substance are added to the alkaline silicic acid aqueous solution obtained in the following steps to prepare a raw material solution.

[0041] a) Heating and pressurizing of silicon dioxide in alkaline aqueous solution

[0042] Silicon dioxide can be synthesized from metal silicon, synthesized from silicon compounds, natural products, etc. In particular, substances synthesized from metal silicon are preferred because it is easy to obtain high-purity metal silicon as a raw material. For example, a powdered granular body composed of silicon dioxide obtained by a method of burning metal silicon powder (so-called VMC method) can be used. Here, by using a powdered granular body as silicon dioxide, the specific surface area becomes larger, and the dissolution rate in the alkaline substance aqueous solution can be increased.

[0043] The alkaline substance contained in the alkaline substance aqueous solution for dissolving silicon dioxide can be directly the above alkaline substance, or can be an alkaline substance other than the above (other alkaline substance). When other alkaline substances are used, the other alkaline substances used are preferably removed by washing or ion exchange after dissolving silicon dioxide.

[0044] As a method for dissolving silicon dioxide in an aqueous solution of an alkaline substance, the boiling point of the aqueous solution of the alkaline substance is raised by pressurizing and the solution is maintained at a temperature above the boiling point under normal pressure. For example, a condition of heating at 180° C. while pressurizing can be adopted. As the temperature of dissolution, the dissolution rate can be increased by increasing it, and the pressure can be reduced by reducing it, so the dissolution equipment can be simplified.

[0045] The dissolved silicon dioxide is preferably 17%, 15%, 10% by weight, and the lower limit is preferably 1%, 3%, 5%. These upper and lower limits can be combined arbitrarily. The concentration of the alkaline substance in the alkaline substance aqueous solution is not particularly limited, and is preferably a concentration that becomes an appropriate alkaline substance concentration when the raw material solution is finally prepared.

[0046] b) Removal of Na ions from an aqueous sodium silicate solution in the presence of an alkaline substance

[0047] The sodium silicate aqueous solution can use water glass obtained by dissolving sodium silicate in water. The alkaline substance can use the above substances. By removing Na ions from the sodium silicate aqueous solution in the presence of the alkaline substance, the sodium in the sodium silicate is replaced by the alkaline substance. The removal of Na ions can be carried out using ion exchange resins, etc.

[0048] The upper limit of the dissolved sodium silicate is preferably 17%, 15%, or 10% in terms of oxide conversion based on the total mass, and the lower limit is preferably 1%, 3%, or 5%. These upper and lower limits may be combined in any manner. The concentration of the alkaline substance in the alkaline substance aqueous solution is not particularly limited, but is preferably a concentration that provides an appropriate alkaline substance concentration when the raw material solution is finally prepared.

[0049] c) dissolving metallic silicon in an aqueous solution containing an alkaline substance and / or a second alkaline substance

[0050] Silicic acid is generated by immersing and dissolving metallic silicon in an aqueous solution in which the alkaline substance and / or the second alkaline substance are dissolved. The metallic silicon is preferably in a powdery or granular form. As a dissolution condition, heating is preferred. As a heating temperature, there is no particular limitation, and 30°C, 40°C, 50°C, 60°C, etc. can be used as a lower limit.

[0051] The upper limit of the dissolved metal silicon, calculated as oxide based on the total mass, is preferably 17%, 15%, or 10%, and the lower limit is preferably 1%, 3%, or 5%. These upper and lower limits may be arbitrarily combined.

[0052] The alkaline substance is the above-mentioned alkaline substance. The second alkaline substance is not particularly limited, and is preferably composed of an organic substance. Examples of the second alkaline substance include dialkylamines (eg, amines having 1 to 3 carbon atoms), trialkylamines (eg, amines having 1 to 3 carbon atoms), and the like.

[0053] The total concentration of the alkaline substance and the second alkaline substance in the aqueous solution containing the alkaline substance and / or the second alkaline substance is not particularly limited. When the alkaline substance is added, the concentration is preferably less than the amount of the alkaline substance present when the raw material solution is finally prepared.

[0054] (Heating process)

[0055] The heating step is a step of heating the raw silica particles contained in the dispersion obtained in the raw silica particle preparation step to form spherical silica particles. It is a step of removing water and organic matter contained in the raw silica particles by heating.

[0056] The heating step is to heat the dispersion directly, to heat the dispersion in which the dispersion medium is replaced by another dispersion medium, and / or to separate the raw silica particles from the dispersion and heat them. The raw silica particles can be separated from the dispersion medium by centrifugation or filtration. After the raw silica particles are separated, the dispersion medium can be replaced by adding another dispersion medium such as water or an organic solvent. By performing multiple replacements of the dispersion medium, the organic matter contained in the dispersion can be more reliably removed.

[0057] The heating process can remove the moisture and organic matter contained in the raw silica particles by heating at a high temperature. First, it is preferred to remove the moisture and organic solvent at a temperature that does not remove the moisture sharply. For example, 40°C, 60°C, 80°C, 100°C, 120°C, 140°C, etc. The pressure can be reduced or air-dried while heating. If a certain degree of moisture is removed, even if heated at a high temperature, the rapid expansion of the moisture will not occur, so it is heated to a temperature that can remove the organic matter. As a temperature that can remove the organic matter, a temperature of 500°C or above is preferred.

[0058] In particular, organic matter can be oxidized and removed by heating in an oxidizing atmosphere such as air, so it is preferred. As the lower limit of the heating temperature, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, etc. can be adopted, and as the upper limit, 1150°C, 1100°C, 1050°C, etc. can be adopted. It is believed that by heating the raw silica particles in a state separated from the dispersion medium, the particles shrink and become dense as the water is separated.

[0059] (Hydrothermal treatment process)

[0060] After the raw silica particle preparation step and before the heating step, it is preferred to have a hydrothermal treatment step in which the dispersion medium of the dispersion is replaced with water and then heated to perform a hydrothermal reaction. The hydrothermal reaction is preferably performed at a temperature of 130°C to 250°C. In particular, the lower limit of the temperature is preferably 100°C, 110°C, and 120°C, and the upper limit is preferably 220°C, 200°C, and 180°C. These upper and lower limits can be arbitrarily combined.

[0061] By performing a hydrothermal reaction, the spherical silica particles finally produced can also be made into hollow particles or porous particles. That is, through the hydrothermal treatment process, the reaction of dissolving the low-density silanol bond inside the particle by the alkaline substance and the reaction of densifying the particle shell due to heat occur in a balanced manner, so it is speculated that the hollow particles and porous particles are generated due to the balance of these two reactions.

[0062] When the hydrothermal treatment step is performed, the raw silica particles are then separated from the dispersion medium and heated as described above to remove organic matter. When the hydrothermal reaction is performed, it is particularly preferred to heat to 900° C. or higher in the heating step to strengthen the hollow particles and porous particles.

[0063] (Other processes)

[0064] The method for producing spherical silica particles of this embodiment may crush the obtained spherical particles or perform surface treatment. Crushing may be performed by a method similar to a conventional pulverization operation. A jet mill or the like is particularly preferred.

[0065] The spherical silica particles manufactured by the manufacturing method of the spherical silica particles of the present embodiment can be surface treated with a surface treatment agent such as a silane compound. Appropriate surface treatment varies depending on the form in which the spherical silica particles are used. When the spherical silica particles are filled into a resin, it is preferred to use a surface treatment agent that can introduce a functional group with high affinity or reactivity with the resin.

[0066] Example

[0067] The method for producing spherical silica particles of the present invention will be described in detail based on the following examples.

[0068] <Sample preparation>

[0069] The test samples of each test example were prepared under the conditions shown in Table 1. The details are described below.

[0070] Test Example 1

[0071] (Raw material silicon dioxide particle preparation process)

[0072] First, an alkaline silicic acid aqueous solution was prepared by mixing 9.0 g of metal silicon powder (volume average particle size 20 μm), 27.0 g of ion exchange water, and 64.0 g of a 25 mass % TMAH aqueous solution, and maintaining the mixture at 40° C. for 48 hours to dissolve the metal silicon, thereby obtaining an alkaline silicic acid aqueous solution containing about 26.3% of silicic acid in terms of silicon dioxide.

[0073] Ion exchange water was added to the obtained alkaline silicic acid aqueous solution in such a manner that the concentration of silicic acid was 4.5% by mass in terms of silicon dioxide. TMAH as an alkaline substance was added in such a manner that the molar ratio was 0.44 based on the silicon element from the contained silicic acid. Then, acetone was added as an organic solvent in such a manner that the molar ratio was 30.6 when mixed with the contained water. Specifically, the ratio of water:acetone was 20:80 in terms of the mass ratio before mixing.

[0074] After sufficient stirring, a 90 mass % acetic acid aqueous solution was added to adjust the pH to 8, and the mixture was further stirred for 30 minutes, whereby raw silica particles were precipitated to form a dispersion.

[0075] (Heating process)

[0076] The obtained dispersion was centrifuged at 5000 rpm for 5 minutes, and the supernatant was removed by decantation and the precipitate was separated. The centrifugation was performed using Model 3700 manufactured by KUBOTA. Ion exchange water of the same mass as the removed supernatant was added and ultrasonic dispersion was performed. Ultrasonic waves were applied at a frequency of 28 kHz and 1000 W for 30 minutes. Centrifugation was performed again under the above conditions, and the obtained precipitate was dried at 130° C. for 1 hour and then calcined at 500° C. for 2 hours. The calcined product was crushed using a mortar until the agglomerate could not be visually observed, and the obtained spherical silica particles were used as the test sample of this test example.

[0077] Test Examples 2 and 3

[0078] The test samples of this test example were obtained by performing the same operation as in test example 1 except that the sintering temperature was 800° C. (test example 2) and 1000° C. (test example 3).

[0079] Test Examples 4 and 5

[0080] a) The amount of alkaline substances present is 0.55 in molar ratio based on silicon element from silicic acid; b) the following hydrothermal treatment process is provided: the dispersion obtained by ultrasonic dispersion after the first centrifugal separation in the heating process is placed in a pressure vessel and subjected to hydrothermal reaction at 175°C for 2 hours; c) the calcination temperature is 800°C (Test Example 4) and 1000°C (Test Example 5); except for this, the test sample of this Test Example is obtained by the same operation as Test Example 1.

[0081] Test Examples 6 to 9

[0082] A test sample of this test example was obtained by the same operation as in Test Example 5 except for the following differences.

[0083] a) Based on the silicon element from silicic acid, the amount of alkaline substance present is 0.44 in molar ratio; b) the pH is set to 6 (Test Example 6), the pH is set to 6 and the temperature during the hydrothermal reaction is set to 200°C (Test Example 7), and only a) (Test Example 8) is changed, the pH is set to 6 and the temperature during the hydrothermal reaction is set to 121°C (Test Example 9).

[0084] Test Examples 10 and 11

[0085] The test sample of this test example was obtained by the same operation as in Test Example 3 except that the amount of the alkaline substance present was 0.35 (Test Example 10) and 0.79 (Test Example 11) in molar ratio based on silicon element derived from silicic acid.

[0086] Test Example 12

[0087] (equivalent to the raw material silica particle preparation process)

[0088] A mixture of 5.2 g of TEOS, 100 g of ion exchange water and 400 g of acetone was prepared. 2.5 g of a 25% by mass TMAH aqueous solution was added to the mixture while stirring. Then, a 90% by mass acetic acid aqueous solution was quickly added to adjust the pH to 8, and the mixture was further stirred for 30 minutes, whereby the raw silica particles were precipitated to form a dispersion. Here, the ratio of ion exchange water to acetone was such that the relative dielectric constant was 30.6. The amount of TMAH added was 0.27 in molar ratio based on the silicon element from the silicic acid derived from TEOS.

[0089] (equivalent to heating process)

[0090] The obtained dispersion was centrifuged at 5000 rpm for 5 minutes, the supernatant was removed by decantation and the precipitate was separated. The centrifugation was performed using Model 3700 manufactured by KUBOTA. Ion exchange water of the same mass as the removed supernatant was added and ultrasonic dispersion was performed. Ultrasonic waves were applied at a frequency of 28 kHz and 1000 W for 30 minutes.

[0091] The obtained dispersion was placed in a pressure vessel and subjected to a hydrothermal reaction at 175°C for 2 hours. Then, centrifugal separation was performed again under the above conditions, and the obtained precipitate was dried at 130°C for 1 hour and then calcined at 1000°C for 2 hours. The obtained calcined product was crushed in a mortar until the agglomerates could not be visually observed, and the obtained spherical silica particles were used as the test sample of this test example.

[0092] Test Example 13

[0093] The same operation as in Test Example 3 was performed except that the content of acetone was 20% when mixed with the contained water. As a result, the generation of particles was not observed in the step corresponding to the step of preparing the raw silica particles, and the heating step was not performed. Therefore, the test sample of this test example could not be obtained.

[0094] Test Example 14

[0095] A test sample of this test example was obtained by the same operation as in Test Example 3 except that the content of acetone was 41.5 when mixed with the contained water.

[0096] Test Example 15

[0097] A test sample of this test example was obtained by the same operation as in Test Example 1 except that the amount of the alkaline substance present was 0.20 in molar ratio based on silicon element derived from silicic acid.

[0098] Test Example 16

[0099] The same operation as in Test Example 1 was performed except that the amount of the alkaline substance present was 0.85 in molar ratio based on the silicon element from silicic acid. As a result, the generation of particles was not observed in the step corresponding to the step of preparing the raw silica particles, and the heating step was not performed. Therefore, the test sample of this test example could not be obtained.

[0100] Test Examples 17 and 18

[0101] The test sample of this test example was obtained by the same operation as in Test Example 5 except that DBU (Test Example 17) and DBN (Test Example 18) were used as the alkaline substance instead of TMAH. It should be noted that the amount of DBU and DBN added was the same as that of TMAH. As a result, the amount of DBU and DBN added was based on the silicon element from silicic acid, and the amount of the alkaline substance present was 0.41 in terms of molar ratio.

[0102] Test Examples 19 and 20

[0103] As the alkaline substance, TEAH (Test Example 19) and TBAOH (Test Example 20) were used instead of TMAH. The test sample of this test example was obtained by the same operation as in Test Example 3. It should be noted that the addition amount of TEAH and TBAOH was the same concentration as that of TMAH. As a result, the addition amount of TEAH and TBAOH was based on the silicon element from silicic acid, and the amount of the alkaline substance present was 0.32 (Test Example 19) and 0.35 (Test Example 20) in terms of molar ratio.

[0104] Test Example 21

[0105] Spherical silica particles were prepared as test samples for this test example using the metal silicon powder used as a raw material for producing the alkaline silicic acid aqueous solution in the raw silica particle preparation step in Test Example 1 and produced by the VMC method. The VMC method is a method for producing spherical silica particles by deflagration of metal silicon powder while it is suspended in the air.

[0106] (evaluate)

[0107] The particle size distribution, specific surface area, pore volume, true specific gravity, number of coarse particles, and impurity content of the test sample of each test example were measured. The results are shown in Tables 1 and 2.

[0108] Particle size distribution: The test sample was dispersed in water at a concentration of 0.5 mass %, and the particle size distribution was measured using a particle size distribution measuring device (SALD-7500nano manufactured by Shimadzu Corporation). For Test Examples 3, 5, 11, and 12, the measured particle size distribution histograms are shown in Table 1. Figure 1 .

[0109] Specific surface area, pore volume: The test sample was measured using an automatic specific surface area / pore distribution measuring device (Tristar 3000, manufactured by Shimadzu Corporation). The specific surface area was measured using the BET 1-point method using nitrogen gas. The pore volume was measured using the value obtained during adsorption using the BJH method.

[0110] True specific gravity: measured using a dry automatic density meter (manufactured by Shimadzu Corporation, AccuPycII1345) using nitrogen. The density of the particle volume including the voids in the spherical silica particles that cannot be penetrated by nitrogen is measured. That is, if there are voids, the density of the spherical silica particles is reduced only by the volume of the voids.

[0111] Number of coarse particles: For each test sample of Test Examples 3, 5, and 21, the number of particles having a particle diameter of 3 μm or more per 1 g was measured using an automatic flow particle imaging analyzer (FPIA-3000 manufactured by Sysmex Corporation).

[0112] Impurity content: For each test sample of Test Examples 5 and 21, the test sample was dissolved in an acid and then the impurity content was measured by ICP.

[0113] Furthermore, SEM photographs were taken for each test sample of Test Examples 3, 6, 8, 10 to 12, 14, and 17 to 20 ( Figures 2 to 12 ).

[0114]

[0115] [Table 2]

[0116]

[0117] As is clear from Table 1, in the three groups of a) Test Examples 1 to 3, b) Test Examples 4 and 5, and c) Test Examples 6 to 9, the conditions before firing are the same within each group, and the particle size distribution is the same within each group, but the heating conditions in the subsequent heating process are different within these groups, so the specific surface area values ​​are different.

[0118] That is, when the conditions of the raw material silica particle preparation process are the same, spherical silica particles with the same particle size distribution can be obtained. The specific surface area is different due to the difference in the temperature during heating after the dispersion medium is removed in the subsequent processing steps (temperature during hydrothermal reaction, calcination temperature). As the reason for the different specific surface areas, it is believed that the pore structure of the manufactured spherical silica particles, especially the pore structure on the surface, changes.

[0119] In Test Example 12, in which spherical silica particles were produced from TEOS, the particle size was uniform, whereas in the test samples of Test Examples 1 to 11 and 17 to 20, in which spherical silica particles were produced from silicic acid, the particle size distribution was broadened. Specifically, it was found that the particle size of the test sample of Test Example 12 was very uniform. The particle size distribution of the particles of Test Example 12 was uniform, with D90 / D50 being about 1.26 or more. Figure 7 This is confirmed by the SEM images shown.

[0120] In contrast, in the test samples of Test Examples 1 to 11 and 17 to 20, even Test Examples 4 and 5, which have the smallest D90 / D50, have a value of 1.67 and contain particles of various particle sizes. Figures 2 to 6 and Figures 8 to 12 Clearly the particle size is not uniform.

[0121] Therefore, in the test samples of Test Examples 1 to 11 and 17 to 20, it can be expected that the filling property of the obtained spherical silica particles in the resin, slurry, etc. is improved. Figure 1 As can be seen from the histogram shown, the particle size is uniform in the test sample of Test Example 12 using TEOS as the raw material, but the particle size varies in the test samples of Test Examples 3, 5, and 11.

[0122] The specific gravity of silicon dioxide is 2.3 g / cm 3 The true specific gravity of Test Examples 1 to 3, 10, 11, 19, and 20 without hydrothermal reaction was 2.3 g / cm 3 In contrast, the true specific gravity of Test Examples 4 to 6, 17, and 18, which underwent hydrothermal reaction, was less than 2.3 g / cm 3 , it can be seen that there are gaps inside that are not connected to the outside.

[0123] It should be noted that among the test samples subjected to the hydrothermal reaction, for Test Examples 7 to 9, the true specific gravity was 2.3 g / cm 3 The values ​​are equivalent to those of particles without voids. However, in these test samples, it is clear from the fact that their pore volumes and specific surface areas are large that the generated voids communicate with the outside, and the true specific gravity is considered to be the same as that of silica.

[0124] The presence or absence of voids (pores) connected to the outside due to different preparation conditions can also be confirmed by SEM photos. Figure 2 It can be seen that no voids (pores) communicating with the outside are observed. Figure 3 It can be seen that although it is confirmed that there are particles with pores, there are almost no pores as a whole. Figure 4 It can be seen that the majority of particles have pores.

[0125] That is, it can be seen that in the test sample of Test Example 8, voids are formed inside like hollow particles, but since these voids are connected to the outside, the true specific gravity becomes the same as that of solid particles. Furthermore, although the details are not shown, if the cross section of the test sample of Test Example 5 is confirmed, it can be seen that a large number of voids are formed in a porous state. There is a tendency for the density of fine voids to increase as they approach the center of the particle.

[0126] The mechanism for generating voids inside by using a hydrothermal reaction is presumed to be as follows. When the raw silica particles are converted into spherical silica particles by a hydrothermal reaction, water is slowly released from the outside, so the outside of the particles gradually becomes dense, and then voids are generated inside when water is released from the inside. However, when the particles are fired by rapid heating without a hydrothermal reaction, water is rapidly released from the entire particles and fired, thereby obtaining solid particles without voids inside.

[0127] It is known that when the relative dielectric constant of the mixed solvent of water and the organic solvent is set to 20 (Test Example 13), the silicic acid contained in the raw material solution is dissolved without precipitation. Therefore, it is known that the relative dielectric constant of the mixed solvent must be at least greater than 20.

[0128] When the relative dielectric constant of the mixed solvent of water and an organic solvent is set to 41.5 (Test Example 14), the silicic acid contained in the raw material solution does not undergo particle formation during precipitation but only forms fine aggregates of silicon dioxide ( Figure 8 ). Therefore, it can be known that the relative dielectric constant of the mixed solvent must be at least lower than 41.5.

[0129] In Test Example 15, in which the amount of alkaline substance added was set to 0.20 in terms of molar ratio to elemental silicon derived from silicic acid, the silicic acid contained in the raw material solution was not particulated during precipitation but only formed fine aggregates of silicon dioxide. Therefore, it is known that the amount of alkaline substance added must be set to more than 0.20 in terms of molar ratio to elemental silicon derived from silicic acid.

[0130] In Test Example 16, in which the amount of alkaline substance added was set to 0.85 in molar ratio relative to silicon element derived from silicic acid, it was found that the silicic acid contained in the raw material solution was dissolved without precipitation. Therefore, it was found that the amount of alkaline substance added must be set to less than 0.85 in molar ratio relative to silicon element derived from silicic acid.

[0131] It can be seen that even if DBU (Test Example 17), DBN (Test Example 18), TEAH (Test Example 19), or TBAOH (Test Example 20) is used instead of TMAH as the alkaline substance, spherical silica particles can be generated in the same manner as TMAH. Figures 9 to 12 ).

[0132] The number of coarse particles was measured for Test Examples 3, 5, and 21. It was found that the number of coarse particles was 2,000 or more in the spherical silica particles of Test Example 21 produced by the conventional VMC method, whereas the number of coarse particles was as small as 5 and 36 in Test Examples 3 and 5, respectively.

[0133] The impurity content of Test Examples 5 and 21 was measured. The results showed that the content of Th and U was reduced to less than 1 / 10 compared with the spherical silica particles of Test Example 21 manufactured by the conventional VMC method, which can reduce the influence of α rays when used in electronic equipment. In addition, there is also a tendency for other measured elements to be roughly reduced. It is speculated that this is because in Test Example 5, impurities did not precipitate when the metal silicon powder was dissolved once and then precipitated.

[0134] (Other tests)

[0135] In the above test examples, metal silicon powder was used as a raw material for preparing the alkaline silicic acid aqueous solution, but it was also confirmed that spherical silicon dioxide particles can be produced even if silicon dioxide particles and water glass (sodium silicate aqueous solution) are used. After preparing the alkaline silicic acid aqueous solution from the respective materials of silicon dioxide and sodium silicate aqueous solution, the same spherical silicon dioxide particles as those in the case of using metal silicon powder can be obtained by performing the same operation as in the case of using metal silicon powder.

[0136] Methods using silica particles

[0137] 20.0 g of silica powder (product name: SO-E2, manufactured by Yaduma Technology Co., Ltd.), 15.0 g of ion-exchanged water and 64.0 g of a 25 mass % TMAH aqueous solution were mixed and maintained at 180° C. for 1 hour in a pressure vessel to dissolve the silica, thereby obtaining an alkaline silicic acid aqueous solution containing approximately 20.2% of silicic acid calculated as silica.

[0138] Method using sodium silicate aqueous solution

[0139] 10.2 g of sodium silicate aqueous solution (water glass) and 15.0 g of ion exchange water were mixed and stirred at 40° C. for 4 hours. Then, 64.0 g of 25% by mass TMAH aqueous solution was added dropwise while removing Na ions by ion exchange. As a result, an alkaline silicic acid aqueous solution containing 10.8% by mass of silicic acid in terms of silicon dioxide was obtained.

Claims

1. A method for producing spherical silica particles, comprising: a raw silica particle preparation step of preparing a dispersion of raw silica particles from a raw material solution in which silicic acid is dissolved in a mixed solvent of water and an organic solvent in the presence of an alkaline substance consisting of at least one of a quaternary ammonium and a base having a cyclic amidine structure; and a heating step of heating the dispersion or the raw silica particles obtained by solid-liquid separation from the dispersion to remove organic matter contained in the dispersion to prepare spherical silica particles; The relative dielectric constant of the mixed solvent is 21 to 40, Furthermore, the quaternary ammonium derived from the alkaline substance is blended at a molar ratio of 0.3 to 0.8 with respect to the silicon element derived from the silicic acid.

2. The method for producing spherical silica particles according to claim 1, wherein The organic solvent is one or more solvents selected from the group consisting of acetone, methyl ethyl ketone and ethyl acetate.

3. The method for producing spherical silica particles according to claim 1 or 2, wherein: The alkaline substance is one or more compounds selected from the group consisting of quaternary ammonium having 4 to 16 carbon atoms, diazabicycloundecene and diazabicyclononene.

4. The method for producing spherical silica particles according to claim 1 or 2, wherein: The raw material solution is prepared by a raw material solution preparation step of adding the organic solvent and the alkaline substance added as needed to the alkaline silicic acid aqueous solution in the mixing ratio. a) heating and pressurizing the silicon dioxide in the aqueous solution of the alkaline substance, b) removing Na ions from the sodium silicate aqueous solution in the presence of the alkaline substance, and c) obtained by any of the methods of dissolving metallic silicon in an aqueous solution containing the alkaline substance and / or the second alkaline substance.

5. The method for producing spherical silica particles according to claim 1 or 2, wherein: The raw material silica particle preparation step is a step of adjusting the pH of the raw material solution to 7 to 10 to prepare the raw material silica particles.

6. The method for producing spherical silica particles according to claim 1 or 2, wherein: After the raw silica particle preparation step and before the heating step, a hydrothermal treatment step of replacing the dispersion medium in which the raw silica particles are dispersed with water and then heating under pressure at 130° C. to 250° C. is provided. The spherical silica particles produced in the heating step are hollow particles.

7. The method for producing spherical silica particles according to claim 6, wherein: The heating step includes a step of heating at 900° C. or higher.

Citation Information

Patent Citations

  • Silica particles, manufacturing method for same, and silica sol

    CN105813977A

  • Hollow silica particles and method for producing same

    CN109071239A

  • Silicon dioxde acetone dispersion liquor and its preparation method

    CN1800012A

  • Method for producing spherical silica-based mesoporous body

    JP2006027985A

  • Method for manufacturing anisotropic-shape silica sol

    JP2007153671A